Sargassum fusiforme and its fucoidan alleviates high-fat diet induced obesity associated with the improvement of the gut microbiota profile - Xiaoyu Ling; Zhengyang Li; Ning Su; Lingqing Kong; Shiwei Han; Dafeng Song (Journal of Functional Foods)
Obesity is considered a significant global health issue. The gut microbiota plays a crucial role in preventing obesity. Sargassum fusiforme and its fucoidan extract have lipid-lowering effects, but their mechanisms are not yet fully understood. This study investigates the mechanisms by exploring changes in gut microbiota composition, gene expression, and metabolites in mice fed a high-fat diet after intervention with Sargassum fusiforme (SF) and Sargassum fusiforme fucoidan (SFF) through integration of 16S rRNA sequencing, transcriptomics, and non-targeted metabolomics. Our results demonstrate that Sargassum fusiforme can ameliorate high-fat diet-induced obesity by decreasing the abundance of specific Firmicutes phylum bacteria, reducing the levels of glycochenodeoxycholic acid, glycoursodeoxycholic acid, glycohyodeoxycholic acid, and glycodeoxycholic acid, and regulating the expression of the Elovl3, Gm3734, Per2, and Tnnc1 genes. This offers a new perspective for hypercholesterolemia treatment strategies.